Development Of Teacher Competence (A Site Study at State Senior High School 2 Kebumen ) - Sundari, Retno (2012)
There are four objectives of this research: (1) to describe the development of pedagogical competence (2) to describe the development of personality competence; (3) to describe the development of Social Competence and (4 to describe the development of professional competence This research is a descriptive qualitative one. Data of the research were gained through interview, observation, documentation, by involving the vice principal of curriculum, the vice principal of public relation, the teachers and the students of the school. The data were analyzed by using an interactive model of analysis. Validity of the data was obtained through extended time of the research, regular observation, triangulation, and interview of key informants. The results of the research show that most of the teachers at the State Senior High School 2 Kebumen have mastered the pedagogical competence, social competence, and professional competence. The development of teachers' competence is meant to fulfil three needs. They are 1) a social need to increase the ability of educational system efficiently and socially, 2) needs to find out ways to develop social potential and academic potential, and 3) needs to develop their personalities. How to develop the pedagogy competence and professional competence is to send the teachers to join seminars, trainings, In House Trainings, courses and workshops. And how to develop personal competence and social competence of teachers are to ask the teachers to join in the students'activities, religion activities, outbonds, fieldtrips, and to ask the teachers to help the poor students. There are some problems to develop the competence: 1) the attitude of teachers who do not support, 2) inadequate infrastructures and facilities, and 3) limited time. Efforts to cope with the problems are to ask the teachers to use E-Learning facilities, to ask the teachers to join in the students'activities, to involve themselves in the religious activities and to participate in the social activities.